2017
DOI: 10.1037/tra0000182
|View full text |Cite
|
Sign up to set email alerts
|

Lower subjective life expectancy in later life is a risk factor for posttraumatic stress symptoms among trauma survivors.

Abstract: These findings suggest that different traumatic experiences, whether belonging to one's past or whether currently ongoing, predict PTSS in later life. Moreover, it appears that subjective time horizons until death, but not subjective age since birth, can buffer against the negative effect of the trauma. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
2
1
1
Order By: Relevance
“…As mentioned, however, contrary to our hypothesis we did not find a significant association between exposure to combat and ATOA. Thus, we were not able to replicate the findings of similar studies that found a direct link between outcomes related to subjective aging and previous trauma, such as subjective age or future orientation and the trauma of war captivity (i.e., Avidor et al, 2017). Differences in subjective aging in the present sample, then, need to be explored in terms of personal predispositions, or vulnerabilities, such as attachment insecurities (i.e., Kadir & Bifulco, 2013).…”
Section: Discussioncontrasting
confidence: 88%
“…As mentioned, however, contrary to our hypothesis we did not find a significant association between exposure to combat and ATOA. Thus, we were not able to replicate the findings of similar studies that found a direct link between outcomes related to subjective aging and previous trauma, such as subjective age or future orientation and the trauma of war captivity (i.e., Avidor et al, 2017). Differences in subjective aging in the present sample, then, need to be explored in terms of personal predispositions, or vulnerabilities, such as attachment insecurities (i.e., Kadir & Bifulco, 2013).…”
Section: Discussioncontrasting
confidence: 88%
“…These findings are in line with previous studies on SNtD and other concepts of subjective time left to live, pointing to the buffering and moderating effect that these notions have when coping with trauma (i.e., Avidor et al, 2017Avidor et al, , 2021. As these studies suggest, a more expansive sense of one's time horizons in the context of trauma may be beneficial as it could indicate the existence of resources and a maintenance of a sense of vitality, which has not been effaced in the shadow of trauma and even PTSS.…”
Section: F I U R Esupporting
confidence: 92%
“…As these studies suggest, a more expansive sense of one's time horizons in the context of trauma may be beneficial as it could indicate the existence of resources and a maintenance of a sense of vitality, which has not been effaced in the shadow of trauma and even PTSS. Thus, a longer sense of time left to live may indicate that in spite of being traumatised, one's sense of the future remains relatively long and intact, with favourable outcomes for one's mental health, as has been seen in previous studies (Avidor et al, 2017(Avidor et al, , 2021Palgi, 2016). The current findings, therefore, add to that body of knowledge revealing that SNtD also interacts with PTSS for predicting hope 1 year later.…”
Section: F I U R Esupporting
confidence: 76%
“…For example, several studies identified heightened loneliness, social stressors, and malnutrition during the corona virus disease 2019 pandemic as contributors to older subjective age ( Schorr et al, 2021 ; Terracciano et al, 2021 ). Adverse social contexts, such as those resulting from armed conflict or natural disasters, exacerbate individual stressors that may accelerate aging ( Avidor et al, 2017 ; Epel, 2004 ; Shrira et al, 2011 ). Accordingly, theories of subjective age can be enriched through analyses of populations that have endured diverse and often severe stressors of armed conflict in their lifetimes.…”
Section: Background and Objectivesmentioning
confidence: 99%